The Anatomy of a Crime Discovery after 25 Years. A Notable Case of Book Theft and its Detection - Jørgensen, Jesper Düring (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
The 11th September 2003 was quite an ordinary working day in the Royal Library - at least for the first few hours in the morning. At approximately 11.00 a.m., however, I was interrupted by the telephone. A polite lady introduced herself as the rare book specialist from Christie’s in London. From a consignor she had received the following work for sale: Propalladia de Bartholome de Torres Naharro. Dirigida... Napoles: por Ioan Pasqueto de Sallo, Naples 1517. Her investigation of a critical edition of Torres Naharro’s works from 1943 had established that only two copies of this particular work were known to exist. One incomplete copy in the National Library of Spain in Madrid, and one complete copy in The Royal Library in Copenhagen. This puzzled the keeper of books at the auction company, and she was keen to know whether she had a historic sensation in her hands or simply a stolen book.